Successful medical management of neutropenic enterocolitis (typhlitis) in a child with acute lymphoblastic leukemia - Ozçay, Figen; Kayiran, Sinan Mahir; Ozbek, Namik (The Turkish Journal of Pediatrics, 2003)
We report a case of acute lymphoblastic leukemia that was complicated by neutropenic enterocolitis (typhlitis) during the initial period of remission-induction chemotherapy. The patient's clinical symptoms resolved after aggressive treatment with intravenous fluids and electrolytes, nasogastric decompression, bowel rest, total parenteral nutrition, broad-spectrum antibiotics, and granulocyte colony-stimulating factor. Netropenic enterocolitis should always be considered in neutropenic leukemic children with the triad of fever, vomiting, and abdominal pain. Gastrointestinal hemorrhage may also accompany the symptoms described above. Plain roentgenogram, ultrasonography and computed tomography of the abdomen are helpful for making the diagnosis of this clinical condition. Early recognition and proper medical management of neutropenic enterocolitis may prevent the need for surgical intervention, and/or be life-saving.